2018
DOI: 10.1080/02670844.2017.1420417
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature plasma treatment of carbon fibre/epoxy resin composite

Abstract: To gain insight into bonded repairs, which are commonly applied to damaged composites, we herein investigate the effects of low-temperature plasma treatment on the surface properties of a carbon fibre/epoxy resin composite, revealing that this treatment enhances the bonding strength between the patch and damaged surface. Moreover, we probe the water contact angle, chemical composition, tensile-shear strength, and morphology of composite surfaces, showing that under optimal conditions, plasma treatment decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…We observed that short-term oxygen plasma treatment approximates the values of contact angles to those obtained for the oxidized layer itself, whereas the values obtained for the carbon coating before plasma modification are similar to those in the initial state. The higher contact angles for the samples after plasma treatment are not typical for those reported in the literature, which point to a decrease in contact angles of different carbon surfaces after plasma treatment [35,36,40].…”
Section: Resultssupporting
confidence: 39%
See 1 more Smart Citation
“…We observed that short-term oxygen plasma treatment approximates the values of contact angles to those obtained for the oxidized layer itself, whereas the values obtained for the carbon coating before plasma modification are similar to those in the initial state. The higher contact angles for the samples after plasma treatment are not typical for those reported in the literature, which point to a decrease in contact angles of different carbon surfaces after plasma treatment [35,36,40].…”
Section: Resultssupporting
confidence: 39%
“…At the nanoscale, plasma treatment increased the surface roughness, but the differences were much smaller. Most researchers observed that plasma leads to an increase in roughness parameters [32], the related surface area, and the amount of surface defects of some carbon structures such as fibers [33,34] or nanotubes [35]. However, they also indicate that an extended treatment duration can result in the opposite effect-smoothening of the surface [34].…”
Section: Resultsmentioning
confidence: 99%
“…Thermoset plastic is of interest for MID substrate because it offers some high heat distortion temperature. The thermoset compound can be mixed with a wide variety of fillers, which allows to modify their properties to meet the requirements for a given applications [ 198 , 199 , 200 , 201 , 202 ]. The addition of suitable proportion of fillers can produce the coefficients of thermal expansion, heat distortion and elongation behaviour virtually identical to those of copper.…”
Section: Thermoset Plastic For Midmentioning
confidence: 99%
“…[ 20–22 ] However, at present, the plasma surface treatment of carbon fibers is mainly carried out in low pressure or air‐free gas environments. [ 23–26 ] On the other hand, a glow discharge is easy to be generated in low pressure or inert gas, but it is difficult to be achieved in atmospheric air because the development of electron avalanches is not easy to control, and the discharge is easily converted to filamentary discharge. Under a low‐pressure environment, vacuum equipment is needed, which makes the system more complex and also causes noise problems.…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials with excellent mechanical properties can be obtained by compounding carbon fibers with polymers, which are widely used in the fields of high‐tech industries and military industries such as aerospace, transportation, biomedical science, and so on. [ 1–4 ] However, due to the nonpolar and highly crystallized graphite layer structure and the lack of functional groups with chemical activity on the surface, the carbon fibers exhibit chemical inertia, resulting in poor bonding between carbon fibers and matrix. [ 5,6 ] Therefore, the application of carbon fibers in special working conditions is greatly limited because the excellent properties of composites are difficult to play.…”
Section: Introductionmentioning
confidence: 99%